The Importance of the Role of Teacher Professionalism in the 21st Century Education Process at SD Segoroyoso Bantul Yogyakarta - Muzfirah, Suci (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2021)
Education is currently in the era of education 4.0 or can be called 21st century education. Where the educational process changes so rapidly with the help of technology. Teachers play an important role in carrying out functions and realizing national educational objectives. The purpose of this research is to see how and to what extent teacher self-reflection has contributed to educational development efforts in the 21st century as a professional teacher. This study involved 2 teachers at SD Segoroyoso Bantul. Where the 2 teachers are already certified and some are not yet certified. The method used is descriptive qualitative method with data retrieval using interviews and documentation. The results of the study can be stated that to become a professional teacher does not have to be certified first. Important components to becoming a professional teacher are 24 teacher administration, 4 teacher competencies (pedagogic, personality, professional, social), understanding the role of the teacher profession, and also understanding learning in the 21st century (education era 4.0).